2010
DOI: 10.2134/agronj2009.0416
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Seeding Rate and Herbicide Treatments on Weed Control, Yield, and Quality of Spring‐Seeded Glyphosate‐Resistant Alfalfa

Abstract: Field trials were conducted in 2005 and 2006 in central and southwest Missouri to investigate the eff ect of seeding rate and herbicide programs on weed control, forage quality, and yield within the year of establishment in spring seeded glyphosate-resistant (GR) alfalfa (Medicago sativa L.). In all experiments, EPTC (4.4 kg ha -1 ), 2,4-DB plus sethoxydim (1.1 plus 0.21 kg ha -1 ), imazamox (0.043 kg ha -1 ) and glyphosate (0.86 kg ae ha -1 ) were applied to GR alfalfa that was seeded at 4.5, 8.9, 13.5, and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 23 publications
4
26
0
Order By: Relevance
“…Over the 5 yr of the study, glyphosate‐treated plots produced 1.5 Mg ha −1 more alfalfa than the non‐glyphosate plots and 7.4 Mg ha −1 more alfalfa than the plots that received no herbicide. This is consistent with findings from McCordick et al (2008) and Bradley et al (2010) who reported higher alfalfa yields from glyphosate‐treated alfalfa than alfalfa treated with a non‐glyphosate herbicide. Total forage yield over the 5 yr of the study was also greater when herbicides were used during alfalfa establishment than when no herbicide was used (Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Over the 5 yr of the study, glyphosate‐treated plots produced 1.5 Mg ha −1 more alfalfa than the non‐glyphosate plots and 7.4 Mg ha −1 more alfalfa than the plots that received no herbicide. This is consistent with findings from McCordick et al (2008) and Bradley et al (2010) who reported higher alfalfa yields from glyphosate‐treated alfalfa than alfalfa treated with a non‐glyphosate herbicide. Total forage yield over the 5 yr of the study was also greater when herbicides were used during alfalfa establishment than when no herbicide was used (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Recently emerged alfalfa seedlings grow relatively slow and are very susceptible to competitive suppression by weeds germinating with or shortly after the crop (Fischer et al, 1988; Gianessi et al, 2002). Weed competition reduces the total‐season alfalfa yield compared to when weeds are controlled with a herbicide (Sheaffer et al, 1988); however, total forage (alfalfa + weeds) yields in the seeding year are often greater when no herbicides are used, due to higher weed yield (Wilson and Burgener, 2009; Bradley et al, 2010; Dillehay and Curran, 2010; Hall et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…prunings from vineyards and grape pomace. Estimations of weed production come from Guzmán et al (2014) except for alfalfa in 1860, which employ values from organic forage (Sheaffer et al, 2014) and in 1999 from conventional farming using the herbicide Lamazox (Bradley et al, 2010).…”
Section: Internal Final Eroi (Or Iferoi) =mentioning
confidence: 99%
“…Temme et al (12) observed 234 lb/acre increase in alfalfa ( Medicago sativa L.) dry matter (DM) yield when instituting herbicide treatments for weed control. Additionally, up to a 21% increase in forage crude protein (CP) has also been observed in legume forage trials where chemical weed control was implemented (3). Experimental applications of herbicides to non‐labeled summer legumes could result in novel findings through forage injury and weed control evaluation.…”
Section: Potential Of Forage Legumesmentioning
confidence: 99%